Popular culture, participation and progression in the literacy classroom - Parry, Becky (Wiley, 2014)
In this paper, I share an account of what happens when a teacher values children's experiences of popular culture in a classroom activity. Drawing on a socio-cultural approach to learning, I suggest that children are not simply enthused when their lived cultures are valued in the classroom but more fundamentally that they are motivated because they can participate in (and are not excluded from) the learning that is constructed. Drawing on data from a recent media literacy research project, I aim to demonstrate the necessity of including popular culture experiences in literacy teaching in order to ensure that children are able to articulate and develop key conceptual understandings. Furthermore, I suggest that interrogatory pedagogic strategies, including practical productions, are key to ensuring that children are able to make explicit, and then organise and develop their conceptual understandings.